ANALISIS ELASTISITAS PERMINTAAN KONSUMEN TERHADAP PRODUK DAN HARGA KERIPIK PADA UKM DI KECAMATAN BATURAJA TIMUR OGAN KOMERING ULU - Styawan Arta; Munajat; Henny Rosmawati (Jurnal Bakti Agribisnis, 2017)
This study aims to calculate the elasticity of consumer demand for changes in the price of SME chips in East Baturaja District, and calculate the elasticity of consumer demand for chips products in East Baturaja District. The study was conducted from March to May 2017 in 3 (three) small and medium enterprises. The research method used is survey method. Sampling method / sample using non probability sampling. The results show the demand for price changes for Rempeyek and banana chips on the changed prices is in elastic or (Ed <1) and the type of sweet potato chips to the changing price are elastic. demand for other products all types of chips have substitution properties similar to those seen in the above explanation are all positive substitutes but the difference is only the percentage of cross elasticity, or has the property (Eq> 0).